2007
DOI: 10.1027/1016-9040.12.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Co-Occurrence of Child and Partner Maltreatment

Abstract: This paper addresses issues in the literature regarding the co-occurrence of partner and child physical maltreatment in the United States and in Europe. Design issues including operationalizations, representativeness of samples, data collection methods, and reference periods are discussed in the context of prevalence studies. Next, possible explanations for the pervasiveness of co-occurring maltreatment are explored with an emphasis on theoretical models and mechanisms of co-occurrence. Finally, we offer asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…In the context of IPV, parents may be less available for comforting children due to their parenting having been undermined by their abusive partner (Bancroft et al, 2011; Knickerbocker, Heyman, Smith-Slep, Jouriles, & McDonald, 2007). In such environments, children may attach with non-parent others, including siblings (Renner, 2012), and may turn to animals for comfort and companionship (DeGue, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of IPV, parents may be less available for comforting children due to their parenting having been undermined by their abusive partner (Bancroft et al, 2011; Knickerbocker, Heyman, Smith-Slep, Jouriles, & McDonald, 2007). In such environments, children may attach with non-parent others, including siblings (Renner, 2012), and may turn to animals for comfort and companionship (DeGue, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Stress and anger produced during conflict among spouses is described as spilling over into the parent -child relationship, resulting in relationships characterized by more harsh, controlling maternal parenting behaviors and higher rates of child-directed aggression (Cox, Paley, & Harter, 2001;Slep & O'Leary, 2005), in addition to an increased likelihood of corporal punishment (Straus & Kantor, 1995). Consistent with this idea, recent work suggests that there is a substantial cooccurrence of partner maltreatment and child abuse (Jouriles, McDonald, Slep, Heyman, & Garrido, 2008;Knickerbocker, Heyman, Slep, Jouriles, & McDonald, 2007), such that an estimated 45% to 70% of children living in physically violent homes are also being physically abused by a parent (Holt, Buckley, & Whelen, 2008). Similarly, Levendosky, Leahy, Bogat, Davidson, and von Eye (2006) found that higher levels of IPV were associated with less ideal observed parenting behaviors, which they captured using a latent variable that included measures of maternal intrusiveness and hostility.…”
Section: Intimate Partner Violencementioning
confidence: 98%
“…Policies should direct resources toward the needs of mother-child dyads. Screening in pediatric settings for abuse of women, as recommended by the American Academy of Pediatrics (Thackeray et al, 2010), is not only an opportunity to intervene to prevent domestic violence and exposure of the child to partner violence but also may be an opportunity to prevent or minimize the risk of child maltreatment by the mother's abuser (Connolly et al, 2006;Edleson, 1999;Guille, 2004;Knickerbocker, Heyman, Slep, Jouriles, & McDonald, 2007;Symes, 2011). Advocates can support establishment and expansion of programs that target the well-being of mother-child dyads.…”
Section: Limitations and Directions For Future Health Care Policy Amentioning
confidence: 99%